2016
DOI: 10.1007/s10147-016-1003-z
|View full text |Cite
|
Sign up to set email alerts
|

Current situation regarding central venous port implantation procedures and complications: a questionnaire-based survey of 11,693 implantations in Japan

Abstract: Upper arm venipuncture with ultrasound guidance seems the most promising technique to prevent complications of central venous port implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…A national Japanese survey by Shiono et al 7 showed an overall incidence of complication rates of 7.3% and 5.2% in forearm and arm implanted ports, respectively. The majority of reported complications in these studies were infections and venous thromboses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A national Japanese survey by Shiono et al 7 showed an overall incidence of complication rates of 7.3% and 5.2% in forearm and arm implanted ports, respectively. The majority of reported complications in these studies were infections and venous thromboses.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 As is the case with breast cancer patients, arm ports in patients who have head and neck tumours and a tracheostomy can potentially reduce infections since the access site in these latter patients is far from tracheal secretions that might facilitate cutaneous bacterial overgrowth increasing the risk of TIVAD pocket infections. [5][6][7][8] Despite these advantages, there are some concerns about a higher incidence of complications in patients with arm port devices as compared to chest ports. 2 Catheter occlusion, upper extremity deep vein thrombosis (UEDVT), skin dehiscence and needle dislocation with drug extravasation are reportedly responsible for the removal of the device in 4%-17% of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled study has confirmed that there are no differences in the incidence of catheter-related thrombotic events or catheter blockage between left-side and right-side port implantation[ 22 ]. Percutaneous puncture methods include blind puncture based on anatomical landmarks, real-time ultrasound guidance and venography, and the ultrasound-guided real-time method, which is currently the most common[ 23 ]. Research has shown that ultrasound real-time guidance can improve puncture efficiency and reduce venous catheter-related infections[ 24 ].…”
Section: Clinical Questionsmentioning
confidence: 99%
“…In 1993, an alternative arm port procedure was introduced by surgeons at the School of Medicine, Yale University 7. The arm ports have some unique advantages compared with chest ports, such as no risk for hemothorax or pneumothorax, lower incidence of arterial puncture,8 better cosmetic outcome,9 and more “bra convenience” 10. These advantages are especially beneficial to breast cancer patients requiring radiotherapy, flap transferring for reconstructive surgeries, as well as those patients with radiodermatitis or compromised respiratory function 11.…”
Section: Introductionmentioning
confidence: 99%